1998
DOI: 10.1073/pnas.95.13.7772
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of insulin-stimulated phosphorylation and activation of the mammalian target of rapamycin mediated by a protein kinase B signaling pathway

Abstract: The effects of insulin on the mammalian target of rapamycin, mTOR, were investigated in 3T3-L1 adipocytes. mTOR protein kinase activity was measured in immune complex assays with recombinant PHAS-I as substrate. Insulin-stimulated kinase activity was clearly observed when immunoprecipitations were conducted with the mTOR antibody, mTAb2. Insulin also increased by severalfold the 32 P content of mTOR that was determined after purifying the protein from 32 P-labeled adipocytes with rapamycin⅐FKBP12 agarose beads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
361
2
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(384 citation statements)
references
References 44 publications
16
361
2
3
Order By: Relevance
“…It is possible that a component involved in mTOR signalling undergoes irreversible inactivation, perhaps by degradation, in apoptotic cells. A possible candidate here is protein kinase B (PKB) which has been implicated in mTOR signalling (Gingras et al, 1998;Scott et al, 1998;Nave et al, 1999) and has recently been shown to be cleaved in apoptotic cells (Rokudai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a component involved in mTOR signalling undergoes irreversible inactivation, perhaps by degradation, in apoptotic cells. A possible candidate here is protein kinase B (PKB) which has been implicated in mTOR signalling (Gingras et al, 1998;Scott et al, 1998;Nave et al, 1999) and has recently been shown to be cleaved in apoptotic cells (Rokudai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In response to insulin and amino acids, mTOR, which is a serine/threonine kinase, phosphorylates and modulates activities of p70 S6 kinase (S6K1 kinase) and an inhibitor of translational initiation, eIF-4E binding protein (46 -48). While insulin activates mTOR and S6K1 kinase via the IRS-1/PI 3-kinase/Akt pathway (49,50), amino acids seem to exert their effect through a direct influence of mTOR (44,51,52). In any event, activation of mTOR and S6K1 kinase causes serine phosphorylation of IRS-1, with a subsequent decline in the IRS-1-associated PI 3-kinase activity (Fig.…”
Section: Serine Phosphorylation Of Irs-1mentioning
confidence: 98%
“…PKC is normally coupled to the IL-2R through PI 3 K, as PKC is activated by PDK1-dependent phosphorylation (40), and a role for PKC in IL-2-mediated signal transduction has been defined using the IL-2-dependent cell line CTLL (59,60). Interestingly, full activation of the PKC-␦ isoform requires the activity of mTOR/FRAP (61), which is in turn dependent on PKB/Akt (62). These two distinct PI 3 K-dependent pathways leading to PKC activation, which can be bypassed using phorbol esters, represent a set of biochemical events that could potentially be defective in the undivided pool.…”
Section: Discussionmentioning
confidence: 99%